1995
DOI: 10.3109/00365529509093290
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Markers of Colonoscopic Activity in Ulcerative Colitis and Crohn's Colitis

Abstract: The highest multiple correlation coefficients were obtained with faecal alpha-1-antitrypsin (r = 0.82) and serum albumin (r = 0.80), and these measurements can be recommended as convenient markers of endoscopic activity in these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 13 publications
0
19
1
Order By: Relevance
“…C-reactive protein, sedimentation rate, white blood cell count, and platelet count are known markers of disease activation in IBD, but their correlation with disease activity is reported to be different in different studies (24)(25)(26)(27)(28)(29). In our study, there was a weak correlation in all UC cases in terms of CRP and TGF-ß1 levels, whereas no correlation was established between the other parameters and TGF-ß1.…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein, sedimentation rate, white blood cell count, and platelet count are known markers of disease activation in IBD, but their correlation with disease activity is reported to be different in different studies (24)(25)(26)(27)(28)(29). In our study, there was a weak correlation in all UC cases in terms of CRP and TGF-ß1 levels, whereas no correlation was established between the other parameters and TGF-ß1.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the results of Adeyemi and Hodgson [ 17] who found no corre lation between haematological parameters of DA and fae cal excretion of the neutrophilderived protein, elastase. Furthermore, when Moran et al [4] assessed DA by endo scopic criteria, haematological parameters, and faecal a r antitrypsin, they found no correlation between the endo scopic appearance and acute-phase reactants. However, a significant correlation was found between faecal a r antitrypsin and the macroscopic evaluation of DA [4],…”
Section: Histological Gradingmentioning
confidence: 99%
“…Saverymuttu et al [3] used faecal excretion of 11'In-labelled granulocytes to assess the DA in patients with UC and found an excellent correlation with both the histological and the endoscopic evaluation. However, both endoscopy and "'Indium-labelled granulocytes arc expensive procedures; therefore, other reliable markers of DA would be useful [4], Calprotectin is a 36-kD calcium-binding protein with antimicrobial properties [5], It has been isolated from the cytosol fraction of polymorphonuclear neutrophils (PMN) and accounts for more than 60% of the protein in the cytosol fraction in such cells [5], Immunohistochemistry has revealed that this protein is located in the cytosol fraction of both PMN and monocytes/macrophages [6,7], Furthermore, clinical investigations have suggested that plasma levels of calprotectin indicate the granulocyte turnover [8,9], Calprotectin can accurately be assessed in plasma and stools by enzyme-linked immunosorbent as say (ELISA) [6. 8-10].…”
Section: Introductionmentioning
confidence: 99%
“…23 A low serum albumin is a useful indicator of mucosal damage, and if low on admission or falls during the ®rst 4 days of attack is associated with increased risk of colectomy. 24,25 A study by Chew et al showed that if there were three or more small bowel loops on abdominal X-ray 73% patients failed to respond to treatment compared to 43% with no ileal loops on X-ray. 26 This observation con®rmed similar ®ndings reported from Italy.…”
Section: Factors Predicting Outcomementioning
confidence: 99%